THERAPY OF GRAVES’ DISEASE WITH SODIUM IODIDE-131 - Hartadi Noor, I Wayan; Saraswati, Made Ratna (E-Jurnal Medika Udayana; vol 2 no 11 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Graves ’ disease is the most common form of thyrotoxicosis, with a peak incidence in the 20-40 year of age group . Females are involved about five times more commonly than male. The easiest sign to recognize patients with Graves ’ disease is the present of Graves’ ophthalmopathy . The diagnosis of Graves’ disease may sometimes base only on a physical examination and a medical history. Diffuse thyroid enlargement and sign of thyrotoxicosis, mainly ophthalmopathy and to lesser extent dermopathy, usually adequate for diagnosis. TSH test combined with F T 4 test is usually the first laboratory test performs in these patients . The patients suffered Graves ’ disease can be treated with antithyroid drug therapy or undergo subtotal Thyroidectomy. Another therapy is by using s odium i odid e -13 1, where this therapy has advantages includ ing easy administration, effectiveness, low expense, and absence of pain. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Graves’ disease, Sodium Iodide-131